Feasibility of Rapid Case Ascertainment for Cancer in East Africa: An Investigation of Community-Representative Kaposi Sarcoma in the Era of Antiretroviral Therapy. (October 2021) - Semeere, Aggrey; Byakwaga, Helen; Laker-Oketta, Miriam; Freeman, Esther; Busakhala, Naftali; Wenger, Megan; Kasozi, Charles; Ssemakadde, Matthew; Bwana, Mwebesa; Kanyesigye, Michael; Kadama-Makanga, Philippa; Rotich, Elyne; et al.
Abstract: Background: Rapid case ascertainment (RCA) refers to the expeditious and detailed examination of patients with a potentially rapidly fatal disease shortly after diagnosis. RCA is frequently performed in resource-rich settings to facilitate cancer research. Despite its utility, RCA is rarely implemented in resource-limited settings and has not been performed for malignancies. One cancer and context that would benefit from RCA in a resource-limited setting is HIV-related Kaposi sarcoma (KS) in sub-Saharan Africa. Methods: To determine the feasibility of RCA for KS, we searched for all potential newly diagnosed KS among HIV-infected adults attending three community-based facilities in Uganda and Kenya. Searching involved querying of electronic medical records, pathology record review, and notification by clinicians. Upon identification, a team verified eligibility and attempted to locate patients to perform RCA, which included epidemiologic, clinical and laboratory measurements. Results: We identified 593 patients with suspected new KS. Of the 593, 171 were ineligible, mainly because biopsy failed to confirm KS (65%) or KS was not new (30%). Among the 422 remaining, RCA was performed within 1 month for 56% of patients and within 3 months for 65% (95% confidence interval: 59 to 70%). Reasons for not performing RCA included intervening death (47%), inability to contact (44%), refusal/unsuitable to consent (8.3%), and patient re-location (0.7%). Conclusions: We found that RCA ― an important tool for cancer research in resource-rich settings ― is feasible for the investigation of community-representative KS in East Africa. Feasibility of RCA for KS suggests feasibility for other cancers in Africa.